TARQIYAT AL-LUGHAH AL ‘ARABIYAH: ISTIKHDAM AL-KUTUB AL-TAFA’ULIYAH LI MUKAFAKHAT QALAQ AL-QIRAAH: ترقية اللغة العربية: استخدام الكتب التفاعلية لمكافحة قلق القراءة - Abdul Basith; Anyes Lathifatul Insaniyah (Lahjah Arabiyah : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
This research was conducted to address the critical issue of Arabic reading anxiety, which hinders students' motivation, participation, and academic achievement. The main reason is that learning approaches specifically designed to reduce emotional and cognitive complexity in Arabic language learning are not yet optimal. The research uses a mixed methods approach with a sequential explanatory design. The quantitative stage consists of a quasi-experiment (pretest-posttest control group), while the qualitative stage includes participant observation, in-depth interviews, and document analysis. Quantitatively, the interactive book-based gamification intervention successfully reduced reading anxiety by 50%, increased motivation by 57.5%, and raised the average score from 70 to 85. Qualitative findings reveal that gamification creates a low-threat learning environment, fulfils the psychological needs of autonomy-competence-relatedness, and facilitates cognitive processing. However, 20-25% of students were less responsive, indicating variations in individual needs. Integrating gamification with interactive textbooks has proven effective as a transformative strategy to reduce Arabic reading anxiety while simultaneously increasing engagement and learning outcomes. This research recommends the implementation of an adaptive learning model that considers students' personal needs, as well as the need for further research with a broader scope.